IMPROVING EDUCATION AND BUILDING DIGITAL LITERACY IN STUDENTS WITH AUTISM SPECTRUM DISORDER (ASD): TEACHER APPROACHES AND OBSTACLES - Nor Amalina Rusli, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study aims to explore the role of educational reform in enhancing digital literacy skills among students with Autism Spectrum Disorder (ASD), focusing on teacher strategies and the challenges faced during implementation. With the increasing importance of digital literacy in modern education, students with ASD often face unique barriers in acquiring these skills. As digital technologies become a critical part of both academic and social life, it is crucial to understand how educational reforms can support these students. This research fills a significant gap in literature by examining the intersection of ASD, digital literacy, and the evolving educational landscape. The methodology involves semi-structured interviews with 13 teachers who work with students with ASD in various educational settings. These interviews provide qualitative insights into the strategies teachers employ to develop digital literacy skills in these students, as well as the challenges they face. The findings reveal that teachers utilise individualised approaches, including visual aids, task breakdowns, and technology-assisted learning tools, to enhance digital literacy. However, challenges such as lack of resources, insufficient training, and the need for a more tailored curriculum persist. Despite these hurdles, teachers report positive impacts on students’ engagement and learning outcomes when digital literacy is integrated thoughtfully. In conclusion, while educational reforms show promise in improving digital literacy for students with ASD, there is a pressing need for targeted professional development, adequate resources, and a more inclusive curriculum to address existing barriers and maximise the potential of these students. The study emphasises the importance of continued support and innovation in teaching strategies for this diverse group.